Competition in the market of medical services of Ukraine - Yershov, Serhii (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The paper purpose is to study the features of competition in the Ukrainian medical services market.Findings. The paper highlights the possibilities and limitations of using competitive mechanisms in the health-care sector. The urgency of the issue is caused by the contradiction between the traditional concepts on the ineffectiveness of competition in the health sector and the low performance of the public health system, which raises competition tools’ introduction into this area.Research limitations/implications. Free competition in the healthcare market is achieved under two main conditions: when any medical organization provides a widespread medical service and when there is a large number of healthcare providers in a certain area. Producer competition leads to a reduction in the cost of medical services. As a conclusion, the ways to improve the development of competition in the market of medical services have been developed:Organization of the possibility of free access to the market of medical services.Implementation and development of public-private partnership in the health care system.Organization of transparent competition between providers of health services of all forms of ownership.Involvement of private providers of medical services in the implementation of the state order.Development of marketing plan by private medical organizations.Originality/value. The impact of other markets on the market of medical services is analyzed. The directions for improving the development of competition in the medical services market have been developed.